Ultra-Wideband Communication System with High Data Rate - Immoreev, I.J.; Sudakov, A.A. (Радиофизика и радиоастрономия, 2002)
The ultra-wideband communication system with high data rate is considered. Information in the system is transmitted by train of short pulses, which have duration about 1.0 ns. The hardware realization of the system is offered. The simulation of the system operation is presented.